Babaçu livre e queijo serrano: histórias de resistência à legalização da violação a conhecimentos tradicionais - PORRO, Noemi Sakiara Miyasaka (2015)
This article is about experiences carried out by communities whose ways of life generate and sustain traditional knowledge, in contexts of incorporation of international conventions into the Brazilian juridical system. Case studies on babaçu breaker women, in the State of Maranhão, and Serrano Cheese producers, in the State of Rio Grande do Sul, reveal the meanings of the tradition imbued in the knowledge to be protected. Empirical data analyzed under juridical and anthropological perspectives elicit, in spite of the apparent progress in the legislation, threats to multiple dimensions of ways of life grounded on traditional territories. Without effective, immediate and integral application of the ILO Convention 169, current initiatives of implementation of conventions and laws related to traditional knowledge may have opposite results. We conclude that traditional communities resist illegal appropriation of their knowledge, while interested private sectors search for the support of the rule of law to legitimize plundering.